Charter and Revised Ordinances of Boise City, Idaho 117 (1894) - (:unkn) unknown (My University, 1877)
§ 31: Prohibited keeping or storing in any building, store, or warehouse, within Boise City in any quantity larger than fifty pound. Also prohibited keeping any giant powder, nitro-glycerine, gun cotton, Herculese powder, dynamite, or other material or substance of equal explosive force by whatever known name. Violators fined not less than twenty-five nor more than one hundred dollars, or imprisoned not less than ten nor more than twenty days, or both with costs of prosecution.
Keywords: GUNPOWDER - STORAGE